Analyzing Software Architecture Based on Statechart Semantics - Dias, Marcio; Vieira, Marlon; Richardson, Debra (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2001)
High assurance architecture-based and component-based software development relies fundamentally on the quality of the components of which a system is composed and their configuration. Analysis over those components and their integration as a system plays a key role in the software development process. This paper describes an approach to develop and assess architecture and component-based systems based on specifying software architecture augmented by statecharts representing component behavioral specifications. The approach is applied for the C2 style and associated ADL and is supported within a quality-focused environment, called Argus-I, which assist specification-based analysis and testing at both the component and architecture levels.